The Influence of Leadership Style and Work Ethic on Employee Performance (Case Study of a Manufacturing Company) - Sylvia sisca harlena; Istianah Setyaningsih (Penerbit Hellow Pustaka, 2025)
This study aims to determine the influence of Leadership Style and Work Ethic on Employee Performance at PT. Samjin Indonesia. The method used in this study is quantitative. Data collection was conducted using primary data from questionnaires distributed to employees. The population in this study was 955 people, and the sampling technique used the Slovin formula with a 5% error rate, resulting in a sample of 282 respondents. The analytical method used was multiple linear regression analysis with normality, multicollinearity, and heteroscedasticity tests. Hypothesis testing was conducted using t-tests, F-tests, and coefficient of determination analysis. Based on the results of the partial test, it was shown that Leadership Style (X1) and Work Ethic (X2) partially exhibit a positive and significant influence on Employee Performance (Y) at PT. Samjin Indonesia, with calculated t-values ​​of 2.400 and 12.382, respectively, > from the t-table of 1.969. Meanwhile, the results of the simultaneous test showed a calculated F-value of 125.442 > from the F-table of 3.03, so that Leadership Style (X1) and Work Ethic (X2) simultaneously have a significant effect on Employee Performance (Y). The coefficient of determination (R²) value of 0.473 indicates an influence of 47.3%, while 52.7% is influenced by other variables not examined in this study.